Posthuman Identity and Gender in Hannu Rajaniemi’s The Quantum Thief - Habib, Talha; Tahir, Sana (Pakistan Journal of Humanities and Social Sciences, 2025)
This research paper discusses posthuman identity and gender dynamics in Hannu Rajaniemi’s novel The Quantum Thief. A qualitative textual analysis is used to analyse the themes of subjectivity, gender, memory, and hybridity. Drawing on Rosi Braidotti's posthuman theory, the study explores how the chosen novel questions traditional humanist concepts of the self and gender. A comprehensive analysis of themes such as subjectivity, power, and gender has revealed how advanced posthuman technologies shape subjectivity and challenge traditional gender roles and norms. Characters such as Jean le Flambeau and Mieli are examined deeply, whose identities are influenced and shaped by technological advancements, systemic control, memory manipulation, and contested agency. The research outcomes emphasise the need to reassess human identity and gender in a technology-driven era. The findings contribute to the fields of posthumanism and gender studies. It can be especially helpful in science fiction studies, as it offers insights into the evolving nature of identity in a technologically advanced future.